Convective drying of papaya (Carica papaya L. 'Red Maradol') and banana (Musa acuminata (AAA Group) 'Gros Michel') (Nexo Revista Científica, 2023)
In this study, the drying kinetics of papaya (Carica papaya L. 'Red Maradol') and banana (Musa acuminata (AAA Group) 'Gros Michel') was experimentally investigated in a lab-scale tunnel dryer. The drying experiments were performed at three air temperatures (50, 60, and 70 °C) and three air velocities (1.0, 1.5, and 2.0 m/s). A surface area shrinkage linear model from the literature was used to include the shrinkage effect on the drying process. From the drying curves, no constant rate period was observed and drying occurred in a falling rate period. It was found that the changes in air velocity had a slight effect on the drying process. In addition, a non-linear regression analysis was employed to determine the characteristic drying curve.